2014
DOI: 10.1016/j.compchemeng.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Solving linear and quadratic programs with an analog circuit

Abstract: We present the design of an analog circuit which solves linear programming (LP) problems. In particular, the steady-state circuit voltages are the components of the LP optimal solution. The paper shows how to construct the circuit and provides a proof of equivalence between the circuit and the LP problem. The proposed method is used to implement a LPbased Model Predictive Controller by using an analog circuit. Simulative and experimental results show the effectiveness of the proposed approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…By composing the elementary circuits of the previous section we can design an analog circuit which implements the constraints A eq V = b eq and A ineq V ≤ b ineq . By using simple energy arguments, in [17] it was shown that such circuit would minimize a cost function…”
Section: Quadratic Cost Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…By composing the elementary circuits of the previous section we can design an analog circuit which implements the constraints A eq V = b eq and A ineq V ≤ b ineq . By using simple energy arguments, in [17] it was shown that such circuit would minimize a cost function…”
Section: Quadratic Cost Functionmentioning
confidence: 99%
“…, a constant voltage source and a diode for inequality nodes. [17] for additional details). The redundant constraints are implemented using a simple circuit depicted in Fig.…”
Section: Quadratic Cost Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…More relevant to our work, Vichik and Borrelli design an analog circuit to solve linear and quadratic programming problem, where unknown variables are directly modeled by node voltages and each constraint is specified by a dedicated circuit component [30]. The node voltages representing unknown variables are driven towards their optimal value subjected to the circuit constraints.…”
Section: Related Workmentioning
confidence: 99%